On the empirical content of carbon leakage criteria in the EU Emissions Trading Scheme - Martin, Ralf; Muûls, Mirabelle; de Preux, Laure B.; Wagner, Ulrich J. (Ecological economics, 2014)
The EU Emissions Trading Scheme continues to exempt industries deemed at risk of carbon leakage from permit auctions. Carbon leakage risk is established based on the carbon intensity and trade exposure of each 4-digit industry. Using a novel measure of carbon leakage risk obtained in interviews with almost 400 managers at regulated firms in six countries, we show that carbon intensity is strongly correlated with leakage risk whereas overall trade exposure is not. In spite of this, most exemptions from auctioning are granted to industries with high trade exposure to developed and less developed countries. Our analysis suggests two ways of tightening the exemption criteria without increasing relocation risk among non-exempt industries. The first one is to exempt trade exposed industries only if they are also carbon intensive. The second one is to consider exposure to trade only with less developed countries. By modifying the carbon leakage criteria along these lines, European governments could raise additional revenue from permit auctions of up to €3billion per year, based on a permit price of €30.